VD_FINDINFO HC / 2014 / 306 vom 28. März 2014 - VD Tribunal cantonal (2014)
DÉCISION D'IRRECEVABILITÉ, SUSPENSION DE LA PROCÉDURE, LITISPENDANCE | 27 CL (2007), 126 CPC (CH), 319 let. b ch. 2 CPC (CH)